Synthesis and biological evaluation of novel benzothiazole derivatives as potential anticancer and antiinflammatory agents - Xu, Xuemei; Zhu, Zhaojingtao; Chen, Siyu; Fu, Yanneng; Zhang, Jinxia; Guo, Yangyang; Xu, Zhouyang; Xi, Yingying; Wang, Xuebao; Ye, Faqing; Chen, Huijun; Yang, Xiaojiao (Frontiers in Chemistry, 2024)
Introduction: Cancer, a significant global health concern, necessitates innovative treatments. The pivotal role of chronic inflammation in cancer development underscores the urgency for novel therapeutic strategies. Benzothiazole derivatives exhibit promise due to their distinctive structures and broad spectrum of biological effects. This study aims to explore new anti-tumor small molecule drugs that simultaneously anti-inflammatory and anticancer based on the advantages of benzothiazole frameworks. Methods: The compounds were characterized by nuclear magnetic resonance (NMR), liquid chromatograph-mass spectrometer (LC-MS) and high performance liquid chromatography (HPLC) for structure as well as purity and other related physicochemical properties. The effects of the compounds on the proliferation of human epidermoid carcinoma cell line (A431) and human non-small cell lung cancer cell lines (A549, H1299) were evaluated by MTT method. The effect of compounds on the expression levels of inflammatory factors IL-6 and TNF-α in mouse monocyte macrophages (RAW264.7) was assessed using enzyme-linked immunosorbent assay (ELISA). The effect of compounds on apoptosis and cell cycle of A431 and A549 cells was evaluated by flow cytometry. The effect of compounds on A431 and A549 cell migration was evaluated by scratch wound healing assay. The effect of compounds on protein expression levels in A431 and A549 cells was assessed by Western Blot assay. The physicochemical parameters, pharmacokinetic properties, toxicity and drug similarity of the active compound were predicted using Swiss ADME and admetSAR web servers. Results: Twenty-five novel benzothiazole compounds were designed and synthesized, with their structures confirmed through spectrogram verification. The active compound 6-chloro-N-(4-nitrobenzyl) benzo[d] thiazol-2-amine (compound B7) was screened through a series of bioactivity assessments, which significantly inhibited the proliferation of A431, A549 and H1299 cancer cells, decreased the activity of IL-6 and TNF-α, and hindered cell migration. In addition, at concentrations of 1, 2, and 4 μM, B7 exhibited apoptosis-promoting and cell cycle-arresting effects similar to those of the lead compound 7-chloro-N-(2, 6-dichlorophenyl) benzo[d] thiazole-2-amine (compound 4i). Western blot analysis confirmed that B7 inhibited both AKT and ERK signaling pathways in A431 and A549 cells. The prediction results of ADMET indicated that B7 had good drug properties. Discussion: This study has innovatively developed a series of benzothiazole derivatives, with a focus on compound B7 due to its notable dual anticancer and anti-inflammatory activities. B7 stands out for its ability to significantly reduce cancer cell proliferation in A431, A549, and H1299 cell lines and lower the levels of inflammatory cytokines IL-6 and TNF-α. These results position B7B7 as a promising candidate for dual-action cancer therapy. The study’s mechanistic exploration, highlighting B7’s simultaneous inhibition of the AKT and ERK pathways, offers a novel strategy for addressing both the survival mechanisms of tumor cells and the inflammatory milieu facilitating cancer progression.